2004
DOI: 10.1007/s00534-003-0874-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasonography is useful for diagnosing pancreatic duct injury and adjacent tissue damage in a patient with penetrating pancreas trauma

Abstract: We report a case of pancreatic injury, caused by a stab wound, in which ductal injury and wound depth were clearly identified by intraoperative ultrasonography. A 65-year-old woman was emergently admitted to our hospital after stabbing herself in the abdomen in a suicide attempt. Preoperative computed tomography (CT) and laboratory examination revealed liver and pancreatic injury with massive abdominal bleeding and free air. Operative findings included injuries of the stomach, small bowel, colon, liver, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Indeed, Schellenberg et al 39 reported a series in which 94% of patients were managed based on visual inspection alone; 6% had intraoperative pancreatography, and the studies were all inconclusive. Intraoperative ultrasound has gained popularity in recent years by trauma and hepatobiliary surgeons, allowing for an efficient and highly sensitive method to evaluate the MPD 40–42 …”
Section: Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Schellenberg et al 39 reported a series in which 94% of patients were managed based on visual inspection alone; 6% had intraoperative pancreatography, and the studies were all inconclusive. Intraoperative ultrasound has gained popularity in recent years by trauma and hepatobiliary surgeons, allowing for an efficient and highly sensitive method to evaluate the MPD 40–42 …”
Section: Algorithmmentioning
confidence: 99%
“…Intraoperative ultrasound has gained popularity in recent years by trauma and hepatobiliary surgeons, allowing for an efficient and highly sensitive method to evaluate the MPD. [40][41][42] E. Treatment: The American Association for the Surgery of Trauma Organ Injury Score is relevant to the management of BPI. Grades I and II (i.e., low grade) injuries are contusions and lacerations that spare the pancreatic duct.…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%
“…25 Intraoperative ultrasound is useful for detecting both pancreatic parenchymal and ductal injury. 26 If these techniques do not reveal injury and suspicion remains high, cholangiopancreatography can be performed 27 ; if the patient is on an angiography table, on-table ERCP or open cholangiopancreatography (e.g., via the gallbladder, transduodenal if duodenal injury is present) can be performed. Alternatively, a damage control strategy can be employed by widely draining the injury, closing the abdomen either primarily or temporarily, caring for the patient in the intensive care unit, and obtaining additional diagnostic data with MDCT, MRCP, or ERCP depending on degree of suspicion and the patient's physiological status.…”
Section: Surgerymentioning
confidence: 99%
“…Intraoperative pancreatography, which will be discussed later in the section on ductal transection, may be used to locate an injury to the main pancreatic duct [13]. Intraoperative ultrasound (IOUS) can also be used to diagnose a parenchymal or ductal laceration [15].…”
Section: Exposurementioning
confidence: 99%